IMPROVING STUDENTS’ READING COMPREHENSION THROUGH PREVIEW, ASK QUESTION, IDENTIFY, READ, AND SUMMARIZE (PAIRS) STRATEGY - Ali, Diana Fitri; Amin, Fatimah Hidayahni; Patak, Andi Anto (Universitas Negeri Makassar, 2022)
This study is a quasi-experimental study aimed at finding improvement in students in teaching English reading skills through previewing, questioning, identifying, reading, and summarizing strategies. The study population consisted of students in Class VIIIA, 15 in the experimental class and 15 in the control class, and all students in Class VIIIB. The research data was collected through the distribution of pre-test and post-test questionnaires. The data were analyzed using SPSS 22. The analysis found that the students' performance improved after implementing the Preview, ask question, Identify, Read, and Summarize strategy in the experimental class. The mean score for the experimental class in the pre-test was 66.67, but the mean score for the class after the test was 89.60. Meanwhile, the mean score for the control class in the pre-test was 61.60, increasing to 82.40 using conventional methods. This means that implementing the PAIRS strategy improves students' reading comprehension. The intensity of each is meaningful at literal, interpretive, and critical levels. The phase encouraged the students to practice and improve their reading comprehension.